Heritability of growth traits in the Asian seabass (Lates calcarifer) - Ye, Baoqing (2019)
Growth is an economically important trait in aquaculture. To improve growth trait of the Asian seabass (Lates calcarifer) we have been carrying out, since 2004, a selective breeding program. This study focuses on growth traits in the F2 fish generation, comprised of offspring from 23 mass crosses from 383 F1 brooders. Using genotyping analysis for 10 microsatellites from both brood stock and progeny we have reconstructed the pedigree of each mass-cross. For F2 generation at 90 days post hatch (dph), we have recorded body weight (BW) for 12,117 individuals and total length (TL), standard length (SL) and condition factor (Ktl and Ksl) for 3530 individuals; and all five traits for 2136 individuals at 270 dph. At 90 dph the average BW was 46.88 ± 20.95 g. Combining pedigree information, recorded growth traits and Restricted Maximum Likelihood method, we have estimated that the narrow sense heritability (h2) in F1 fish for BW, TL, SL, Ktl and Ksl was at, 90 dph, 0.12 ± 0.03, 0.11 ± 0.03, 0.10 ± 0.03, 0.20 ± 0.04 and 0.11 ± 0.03, respectively and, at 270 dph, 0.34 ± 0.07, 0.32 ± 0.07, 0.30 ± 0.06, 0.13 ± 0.04 and 0.11 ± 0.04, respectively. At 90 dph the realised heritability for BW was 0.13. Comparing with F1 generation, the growth performance of F2 fish was increased by 14.4%. Heritability of growth traits will be useful for future genetic improvement programmes of the Asian seabass.